Assessing the Value and Role of Seafood Traceability from an Entire Value‐Chain Perspective. Issue 3 (16th March 2015) - Sterling, Brian; Gooch, Martin; Dent, Benjamin; Marenick, Nicole; Miller, Alexander; Sylvia, Gilbert
Abstract The traceability practices and systems of 48 separate seafood businesses were assessed as part of an evaluation of 9 global seafood value chains (from catch to point of sale to the consumer). The purpose was to gain insights and provide knowledge about the impact of traceability on improving seafood industry business performance, including reducing waste, and enhancing consumer trust. In addition, the project developed and delivered a tool that can be used by stakeholders that are seeking to better understand the return on investment of implementation of traceability practices and solutions. Using structured and semistructured interviews of over 80 individuals, the research revealed that traceability is more highly valued by businesses, regardless of their size, if they engage more often in highly collaborative activities with their suppliers and customers. A survey in 5 nations about consumer perceptions with regards to seafood and the key factors influencing their purchasing decisions delivered insights into the discrete choices that consumers make when buying seafood products. The consumer survey data were incorporated into a "Discrete Choice Simulator" that others can use to compare and contrast the preferences of consumers in these countries and better understand what factors regarding traceability impact on their buying decisions. The research concluded with several recommendations for businesses, governments, and nongovernment organizations.